SAFETY AND SECURITY STUDIES OF RAILWAY LINES WITH PUBLIC ROADS (CASE STUDY OF RAILROAD CROSSING IN THE KENJERAN ROAD OF SURABAYA CITY) - Irwan Mahmudi; Sri Wiwoho Mudjanarko (NAROTAMA UNIVERSITY, 2019)
Railways are a mode of transportation that is being liked by the public because of its efficiency. The train has its own road in the form of rails, it doesn’t mean the train doesn’t intersect other transportation. The train crossing is a conflict area for public road users with train. This includes train crossing at Kenjeran street. The kenjeran street itself is a national road that is quite strategic because it is one of the accesses to the Surabaya-Madura toll road. The research this time aims to find out the security aspects that must be improved at the train crossing kenjeran street. Including rider behaviour at the time of the train crossing. The method used for this research is direct observation of the field and also shares questionnaires to find out if a public road user understands regulations while on a train crossing. The research results of many signs or road markers are incomplete so that many road users do not know that in front of the train crossing. Other public road user behaviour is also a lot of offense.